Oral solitary fibrous tumors: A collaborative clinicopathologic study of 19 cases - Cunha, John Lennon Silva; Cavalcante, Israel Leal; Barros, Elton Fernandes; de Sousa Neto, Sebastião Silvério; Cavalcante, Roberta Barroso; Turatti, Eveline; de Mendonça, Elismauro Francisco; de Albuquerque-Júnior, Ricardo Luiz Cavalcanti; Anbinder, Ana Lia [UNESP]; Fragata da Silva, Décio; Duarte, Ivison Xavier; Nonaka, Cassiano Francisco Weege; et al. (Wiley, 2024)
Objective: To report the clinicopathologic features of 19 oral solitary fibrous tumors (SFTs). Methods: Clinical data were collected from the records of seven pathology services. All cases were re-evaluated by HE staining and confirmed by immunohistochemistry. Results: The series comprised 11 females (57.9%) and 8 males (42.1%), with a mean age of 47.3 ± 14.7 years (range: 22–71 years) and a 1.3:1 female-to-male ratio. Most tumors affected the buccal mucosa (n = 7; 36.8%) and presented clinically as an asymptomatic solitary submucosal well-circumscribed nodule with coloration similar to the oral mucosa. Morphologically, most SFTs (n = 10; 52.6%) exhibited a classic hybrid pattern characterized by a well-circumscribed proliferation of densely cellular areas alternating with hypocellular areas in a variably collagenous vascular stroma. Remnants of accessory salivary glands were observed in two cases (n = 2; 10.5%). All tumors were positive for STAT6 and CD34 (n = 19; 100%). Outcome information was available from 6 patients (31.6%), with clinical follow-up ranging from 6 to 24 months (mean ± SD, 9.5 ± 6.8 months), and none developed local recurrence. Conclusions: Oral SFTs are rare and often clinically misdiagnosed. Pathologists should consider SFT in the differential diagnosis of oral spindle cell tumors. Accurate diagnosis requires careful morphological evaluation supported by immunohistochemical analysis.
Keywords: connective tissue diseases; diagnosis; oral pathology; solitary fibrous tumor